2005
DOI: 10.1007/s00775-004-0619-z
|View full text |Cite
|
Sign up to set email alerts
|

Isoprenoid biosynthesis in chloroplasts via the methylerythritol phosphate pathway: the (E)-4-hydroxy-3-methylbut-2-enyl diphosphate synthase (GcpE) from Arabidopsis thaliana is a [4Fe?4S] protein

Abstract: The mevalonate-independent methylerythritol phosphate pathway is widespread in bacteria. It is also present in the chloroplasts of all phototrophic organisms. Whereas the first steps, are rather well known, GcpE and LytB, the enzymes catalyzing the last two steps have been much less investigated. 2-C-Methyl-D-erythritol 2,4-cyclodiphosphate is transformed by GcpE into 4-hydroxy-3-methylbut-2-enyl diphosphate, which is converted by LytB into isopentenyl diphosphate or dimethylallyl diphosphate. Only the bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 38 publications
3
80
0
4
Order By: Relevance
“…4A) and show diamagnetic ground states of both species. This spectroscopic signature is again indicative for [4Fe-4S] 2ϩ clusters (25,33). Species 3 with ␦ 3 ϭ 0.26 mm/s, ⌬E Q3 ϭ 0.63 mm/s, and a relative contribution of 12% (Fig.…”
Section: Expression and Isolation Of Abce1-mentioning
confidence: 67%
See 2 more Smart Citations
“…4A) and show diamagnetic ground states of both species. This spectroscopic signature is again indicative for [4Fe-4S] 2ϩ clusters (25,33). Species 3 with ␦ 3 ϭ 0.26 mm/s, ⌬E Q3 ϭ 0.63 mm/s, and a relative contribution of 12% (Fig.…”
Section: Expression and Isolation Of Abce1-mentioning
confidence: 67%
“…4B). The isomer shifts of species 1 and 2 are characteristic for Fe 2.5ϩ pairs of [4Fe-4S] 2ϩ clusters (25,33). Fig.…”
Section: Expression and Isolation Of Abce1-mentioning
confidence: 99%
See 1 more Smart Citation
“…5B) showed a slightly asymmetric doublet (97% relative area), which is consistent with a [4Fe-4S] 2ϩ (S ϭ 0) cluster. This species was simulated with two doublets, I and II, at a 3:1 ratio as indicated by Seeman et al (41). The analysis gave the following parameters for these doublets: I, ␦ ϭ 0.47 mm/s and ⌬E Q ϭ 1.00 mm/s and for doublet II, ␦ ϭ 0.48 mm/s and ⌬E Q ϭ 1.34 mm/s.…”
Section: The Eukaryotic Mevalonate (Mva)-dependent Pathway Allowedmentioning
confidence: 99%
“…Recent data has shown that (E)-4-hydroxy-3-methylbut-2-enyl diphosphate synthase (GcpE) and LytB proteins are iron-sulfur proteins containing a [4Fe-4S] 2ϩ cluster after reconstitution of the purified protein (12)(13)(14). GcpE catalyzes the reduction of MEcPP into HMBPP via two successive one-electron transfers (11,13).…”
mentioning
confidence: 99%